DIGITAL MARKETING SOCIALIZATION AND EDUCATION FOR MSMES IN CELUK VILLAGE, SUKAWATI DISTRICT GIANYAR REGENCY - Suparna, Putu; Pratiwi, Nuning Indah; Satria, Wahyu Indra; Fitriani, Sri; Listya, Ni Made (LPPM Univ. Ibn Khaldun Bogor, 2023)
Digital marketing is a promotion activity and market search through digital media online by utilizing various means such as social media. This service program aims to improve knowledge and skills about digital marketing, especially social media, for Small and Medium Enterprises (SMEs) business people to increase sales and profits. Attended by silver craftsman MSME participants in Celuk Village, Sukawati District, Gianyar Regency. The methods used in service program activities, namely; socialization of social media use; sharing experiences and discussions; Next, the practice of creating social media accounts and how to make them attractive to buyers in the form of words, stories, images, and others. The results of service activities show that some business actors actively use social media as a promotional tool and have not separated personal accounts from online store accounts, some MSME participants use it occasionally and the rest of, the participants have never used social media marketing due to lack of technological skills. Overall, participants showed great interest in using social media marketing on an ongoing basis.